Insights into the behaviour of biomolecules on the early Earth: The concentration of aspartate by layered double hydroxide minerals. (1st March 2016) - Grégoire, Brian; Erastova, Valentina; Geatches, Dawn L.; Clark, Stewart J.; Greenwell, H. Christopher; Fraser, Donald G.
Abstract: The role of mineral surfaces in concentrating and facilitating the polymerisation of simple protobiomolecules during the Hadean and Archean has been the subject of much research in order to constrain the conditions that may have led to the origin of life on early Earth. Here we examine the adsorption of the amino acid aspartate on layered double hydroxide minerals, and use a combined computer simulation – experimental spectroscopy approach to gain insight into the resulting structures of the host-aspartate material. We show that the uptake of aspartate occurs in alkaline solution by anion exchange of the dianion form of aspartate, rather than by surface adsorption. Anion exchange only occurs at values of pH where a significant population of aspartate has the amino group deprotonated, and is then highly efficient up to the mineral anion exchange capacity.